DESKRIPSI PENGETAHUAN ALAT PRAKTIKUM KIMIA DAN KEMAMPUAN PSIKOMOTORIK SISWA MAN 1 PONTIANAK - Juvitasari, Putri Maya; Melati, Husna Amalya; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe importance of knowledge of laboratory practicum equipment for labor safety and knowledge of the tools that affect the students psychomotor ability and the implementation of the practicum that requires good of the toolsl to facilitate the lab activities then conducted research to know the knowledge of chemistry practicum and psychomotor ability of students MAN 1 Pontianak . This study aim to described the knowledge of students 'chemical practicum tools and to describe students' psychomotor abilities. The research method used in this research is descriptive method. The sample selected using purposive random sampling technique that is class XI MIPA 3. The data collection tool used is a matter of chemistry practicum knowledge test and student psychomotor ability assessment sheet. Based on the result of the research, it is found that student?s knowledge about chemistry laboratory equipment has average value 74. This value indicates that student succeed with category Good. Psychomotor ability of student to the tools and glassware of chemistry laboratory has the average value of 83. The value indicates that students have psychomotor ability with Good categoryKeywords: Knowladge of Practicum Tools, Psychomotor Ability, Solvent making and dilution.